Descartes' natural philosophy - Gaukroger, Stephen; Schuster, John Andrew, 1947-; Sutton, John, 1965- (Routledge studies in seventeenth-century philosophy, 2000)
The most comprehensive collection of essays on Descartes' scientific writings ever published, this volume offers a detailed reassessment of Descartes' scientific work and its bearing on his philosophy. The 35 essays, written by some of the world's leading scholars, cover topics as diverse as optics, cosmology and medicine, and will be of vital interest to all historians of philosophy or science.